Shifting boundaries of the EU's foreign and security policy: A challenge to the rule of law - Annegret Bendiek; Raphael Bossong (Stiftung Wissenschaft und Politik (SWP), 2019)
Europe's foreign and security policy needs to become more effective. To this end, the executive autonomy of European governments should be maximised, and legal constraints from EU law minimised - this view is only seemingly plausible. Only an EU foreign and security policy anchored in the rule of law based on the EU treaties is realistic and sustainable. The EU is under pressure to meet human rights standards on the one hand, and demands to limit migration on the other. Three trends are evident: First, the EU is making new arrangements with third countries to control migration; second, it is using CFSP/CSDP missions to secure borders; third, the EU agencies Frontex and Europol are increasingly operating in the EU neighbourhood. Current trends in EU foreign and security policy pose a challenge to the protection of fundamental rights. For example, CSDP missions such as the EU operation "Sophia" in the Mediterranean are largely exempt from judicial review by the Court of Justice of the European Union. Lawsuits have already been filed with the European Court of Human Rights and the International Criminal Court against Italy and the EU for aiding and abetting human rights violations in Libya. Anyone who does not respect international law also threatens the rule of law at home. This also applies to the EU. The EU should resume the process of formal accession to the European Convention on Human Rights. The legal limits and performance of the EU's foreign and security policy would be made clearer. The German Council Presidency in 2020 should place the rule of law at the heart of European foreign and security policy.
Keywords: 320